Socio-Economic Conditions and Academic Improvement of Students at the University of Rajshahi: A Review - Hossan, Md. Alomgir (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2025)
This study examines the socio-economic conditions of students admitted to the Department of Political Science at Rajshahi University for the academic year 2023-24. Using a combination of secondary literature and primary data, the research investigates key socio-economic factors influencing students' aspirations, including family income, which is 44% (below 10,000 per month), parental education (only 34% completed secondary education), regional disparities, and gender representation. Our findings show that most of the students admitted into the university are from the grassroots area of the village. We also found gender disparities, though narrowing, persist due to socio-cultural barriers, while students from rural areas (82%) remain demotivated due to infrastructural and resource constraints. By observing these trends within the broader context of Bangladesh's higher education landscape, the study underscores the need for targeted policy interventions to ensure greater equity and inclusivity in higher education in Bangladesh. The analysis provides a nuanced understanding and recommendations of how socio-economic dynamics interact with educational aspirations and institutional practices, offering valuable insights for educators, policymakers, and researchers.